Penerapan Regresi Robust dengan Estimasi-MM dalam Analisis Pengeluaran Internet Rumah Tangga di Provinsi Nusa Tenggara Timur Tahun 2021 - Muhammad Rhevanza Kusnadi; Agung Priyo Utomo (Seminar Nasional Official Statistics, 2022)
The development of information and communication technology has caused very significant changes to become one of the basic human needs in carrying out their daily lives. With the development of the information and communication technology sector, household spendings will increase to meet the needs of the internet. This research uses descriptive analysis method and robust regression analysis of MM estimation. The data used in this study comes from the March 2021 Susenas core and consumption and expenditure modules. From the robust regression results, the average household internet contest is Rp 98,970.74 with a total contribution of 2.27 percent to the total household contest. In general, internet households of school age in East Nusa Tenggara are in rural areas, the last education of the head of the household is less than high school, has a very high household income category, or has less than 4 household members using the internet. person. The amount of household internet expenditure has a significant effect on household income, the last education of the head of the household, the number of household internet users, and the area of ​​residence.